Chasing the dragon and stumbling upon an octopus: A case of heroin-induced leukoencephalopathy and reverse takotsubo cardiomyopathy. (September 2021) - Ahmad, Saad; Whiting, Adrian; Song, David; Reyes, Jonathan Vincent; Ireifej, Branden; Almas, Talal; Lieber, Joseph J.
Abstract: The practice of heating heroin and inhaling its vapors, commonly referred to as "chasing the dragon" has been around for decades, but only gained popularity in the United States in the 1990s. Since then, there have been many documented cases of heroin-induced leukoencephalopathy (HIL) and takotsubo cardiomyopathy (TTC). This case highlights a patient with a history of heroin inhalation who presented with multiple neurological features, including bilateral upper and lower extremity weakness, blurry vision and slurred speech. Symptoms progressively worsened over the course of multiple weeks and brain imaging was consistent with toxic leukoencephalopathy secondary to heroin inhalation. Medical course was complicated by a rare associated feature of HIL: reverse Takotsubo cardiomyopathy (rTTC). Transesophageal echocardiogram demonstrated a classic basal hypokinesis and ballooning characteristic of rTTC. The patient's symptoms were treated as currently there is no guideline directed therapy for HIL or rTTC. This case demonstrated a rare and significant complication of heroin inhalation: HIL and rTTC and described potential therapies currently being studied. Highlights: Heroin-induced leukoencephalopathy (HIL) is a rare neurological complication with possible contribution to the development of reverse Takotsubo cardiomyopathy (rTTC). HIL is a neurologic disorder associated with inhaling heroin vapors. The pathophysiology is poorly understood at this time, but the condition appears to affect mainly white matter in the brain, differentiating from other types of leukoencephalopathies. The diagnosis of rTTC is based on the presence of left ventricular basal hypokinesis or akinesis, acute electrocardiogram abnormalities or elevated troponin levels in the absence of any obstructive coronary disease or myocarditis. While there is currently no treatment regimen for HIL, antioxidants such as vitamin A, C, E, zinc, coenzyme q10, and selenium are usually recommended. However, further studies need to be conducted to assess the efficacy of the antioxidants in these patient populations.